Clinical and radiographic study of orofacial alterations in patients with systemic sclerosis - Marcelo Marcucci; Nitamar Abdala (Sociedade Brasileira de Pesquisa Odontológica, 2009)
Systemic sclerosis (SS) is an autoimmune disease with great repercussions on the hard and soft tissues of the orofacial region. The aim of this study was to investigate the relationship between mandibular osteolysis and mouth opening measurements, duration of disease and presence/absence of teeth. Twenty-five subjects were selected: 15 diagnosed with systemic sclerosis and 10 healthy controls. The SS patients were grouped according to the presence (group I) or absence (group II) of mandibular osteolysis. The healthy subjects served as the control group (III). All of them underwent panoramic radiography on Ortophos® equipment (Siemens) and were clinically examined, with mouth opening measurement. We observed that group I had a longer duration of the disease than group II (p = 0.003). Groups I and II presented the same mean mouth opening. There was an increasing correlation between mouth opening and duration of the disease in group I (p = 0.095), but this was not observed in group II (p = 0.596). There was no correlation between presence/absence of teeth and osteolysis (p > 0.999), or between presence/absence of teeth and side of osteolysis (p = 0.143). We could conclude that osteolysis seemed to develop in patients with a longer duration of the disease, but did not modify the degree of mouth opening in relation to patients without osteolysis, and the presence/absence of teeth was not significant. On the other hand, in the osteolysis cases, the longer the duration of the disease, the greater the opening of the mouth.